ANALISIS LAPORAN KEUANGAN (NPM, ROA, ROE) PADA UMKM RUJAK TOGOK DI DELI SERDANG - Wanda Pardosi; Teguh Satya Wira (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study is motivated by the importance of preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) as a basis for assessing the financial performance of MSMEs. Rujak Togok, an MSME in Deli Serdang Regency, currently employs simple financial record-keeping methods, resulting in suboptimal financial information. This study aims to prepare financial statements based on SAK EMKM, calculate profitability ratios specifically Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) and analyze the financial performance of Rujak Togok over the 2021–2025 period. A quantitative approach with descriptive research methods was employed. Data were collected through observation, interviews, documentation, and literature review, and subsequently analyzed using SAK EMKM-compliant financial statement preparation and profitability ratio analysis. The results indicate that the Net Profit Margin (NPM) increased from 16.03% in 2021 to 16.25% in 2025. Meanwhile, Return on Assets (ROA) declined from 45.90% to 27.03%, and Return on Equity (ROE) fell from 50.19% to 27.51%, driven by asset and equity growth outpacing net profit growth. Overall, the preparation of financial statements in accordance with SAK EMKM and the profitability ratio analysis demonstrate that Rujak Togok’s financial performance is in a reasonably good state, providing a foundation for decision-making and business evaluation. Keyword: SAK EMKM, financial statements, Net Profit Margin, Return on Assets, Return on Equity, financial performance.   Abstrak: Penelitian ini dilatarbelakangi oleh pentingnya penyusunan laporan keuangan yang sesuai dengan Standar Akuntansi Keuangan untuk Entitas Mikro, Kecil, dan Menengah (SAK EMKM) sebagai dasar penilaian kinerja keuangan UMKM. Rujak Togok, sebuah UMKM di Kabupaten Deli Serdang, saat ini menerapkan metode pencatatan keuangan yang sederhana, sehingga menghasilkan informasi keuangan yang kurang optimal. Penelitian ini bertujuan untuk menyusun laporan keuangan berdasarkan SAK EMKM, menghitung rasio profitabilitas khususnya  Net Profit Margin  (NPM),  Return on Assets  (ROA), dan  Return on Equity  (ROE) serta menganalisis kinerja keuangan Rujak Togok selama periode 2021–2025. Pendekatan kuantitatif dengan metode penelitian deskriptif digunakan dalam penelitian ini. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan studi pustaka, kemudian dianalisis menggunakan prosedur penyusunan laporan keuangan sesuai SAK EMKM dan analisis rasio profitabilitas. Hasil penelitian menunjukkan bahwa  Net Profit Margin  (NPM) meningkat dari 16,03% pada tahun 2021 menjadi 16,25% pada tahun 2025. Sementara itu,  Return on Assets  (ROA) menurun dari 45,90% menjadi 27,03%, dan  Return on Equity  (ROE) turun dari 50,19% menjadi 27,51%, yang disebabkan oleh pertumbuhan aset dan ekuitas yang melampaui pertumbuhan laba bersih. Secara keseluruhan, penyusunan laporan keuangan sesuai SAK EMKM dan analisis rasio profitabilitas menunjukkan bahwa kinerja keuangan Rujak Togok berada dalam kondisi yang cukup baik, serta memberikan landasan bagi pengambilan keputusan dan evaluasi usaha. Kata kunci: SAK EMKM, laporan keuangan, Net Profit Margin, Return on Assets, Return on Equity, kinerja keuangan.